TMEM2 inhibits hepatitis B virus infection in HepG2 and HepG2.2.15 cells by activating the JAK–STAT signaling pathway - Zhu, X (Cell Death Dis, 2016)
We have previously observed the downregulation of TMEM2 in the liver tissue of patients with chronic hepatitis B virus (HBV) infection and in HepG2.2.15 cells with HBV genomic DNA. In the present study, we investigated the role and mechanism of TMEM2 in HepG2 and HepG2.2.15 during HBV infection HepG2 and HepG2.2.15. HepG2 shTMEM2 cells with stable TMEM2 knockdown and HepG2 TMEM2 and HepG2.2.15 TMEM2 cells with stable TMEM2 overexpression were established using lentivirus vectors. We observed reduced expression of TMEM2 in HBV-infected liver tissues and HepG2.2.15 cells. HBsAg, HBcAg, HBV DNA, and HBV cccDNA levels were significantly increased in HepG2 shTMEM2 cells but decreased in HepG2 TMEM2 and HepG2.2.15 TMEM2 cells compared with naive HepG2 cells. On the basis of the western blotting results, the JAK–STAT signaling pathway was inhibited in HepG2 shTMEM2 cells but activated in HepG2 TMEM2 and HepG2.2.15 TMEM2 cells. In addition, reduced and increased expression of the antiviral proteins MxA and OAS1 was observed in TMEM2-silenced cells (HepG2 shTMEM2 cells) and TMEM2-overexpressing cells (HepG2 TMEM2 and HepG2.2.15 TMEM2 cells), respectively. The expression of Interferon regulatory factor 9 (IRF9) was not affected by TMEM2. However, we found that overexpression and knockdown of TMEM2, respectively, promoted and inhibited importation of IRF9 into nuclei. The luciferase reporter assay showed that IRF9 nuclear translocation affected interferon-stimulated response element activities. In addition, the inhibitory effects of TMEM2 on HBV infection in HepG2 shTMEM2 cells was significantly enhanced by pre-treatment with interferon but significantly inhibited in HepG2.2.15 TMEM2 cells by pre-treatment with JAK1 inhibitor. TMEM2 inhibits HBV infection in HepG2 and HepG2.2.15 by activating the JAK–STAT signaling pathway.